USAGE PATTERN OF HOUSE BRANDS IN RETAIL TRADE NETWORKS - Yulia Y. Medvedeva (Advanced Engineering Research, 2011)
A new approach to the category of ‘house brands’ as to the marketing tool accelerating the development of retail trade networks is offered. The principal directions of the house brands use in retail networks are specified.